Avaliação em larga escala e formulação de políticas públicas: estudo em uma escola no município de São Bernardo do Campo - Leopoldo, Renata Alves (2020)
In Brazil, some educational evaluations were created to analyse the quality of public and private education, so that, based on them, public policies could be defined to improve Brazilian education. The result of these evaluations is used, in theory, for educational public policies’ formulation or reformulation in both regional and national levels, which are related to that result. It also serves to change educational practices that, eventually, were not satisfactory, considering the result of those evaluations. For example, what contributions are taken from large-scale evaluation SAEB for public’s policy definition in the city of São Bernardo do Campo/SP, assuming the municipal entity's desire to qualify education based on the results of such examinations? Thus, this work intends to analyse the large-scale evaluation SAEB, applied to 5º level’s students at Elementary Education I of a selected school, in 2017, its results and, from them, to identify its contribution in public policies’ formulation or reformulation aimed at that school unit. The research’s fundamental categories are the following: large scale evaluation; public policy making. From epistemological perspective, the research is based in a post-critical theory that considers the educational phenomenon in the historical and contextual scope, in a holistic and relational perspective, considering cultural diversity and social inclusion as determinants factors on public policy definitions. From a methodological view, the approach has a double dimension: qualitative and quantitative scope. Regarding to the first, we analysed the documents on large-scale evaluation that we managed to obtain in our research. As for the second, it focused on the analysis of available data on the analysed school unit and its SAEB’s evaluation applied in 2017. In the wake of this process, we understood that Brazilian schools prioritize their curricula to make students able to take tests. The analysed school, for example, included in its schedules the “simulations’ week” (application of tests used in previous evaluations), intending, clearly, to train students. The content teached to students is moulded to standardized tests, limiting their full training and taking them out of necessary knowledge for a critical and emancipated performance in the society in which they are inserted. Therefore, large-scale evaluations (such as SAEB) are used to standardize an educational system, worldwide established, whose structural and administrative control is entered in the most developed countries of the world, such as USA and Japan. Despite being created to measure the quality and evolution of the teaching-learning process, these evaluations don’t achieve this goal, since what they measure is content and skills that only suitable for the insertion of students in the labour market.